Genomic profiling of climate adaptation in Aedes aegypti along an altitudinal gradient in Nepal indicates nongradual expansion of the disease vector. Issue 2 (21st November 2022) - Kramer, Isabelle Marie; Pfenninger, Markus; Feldmeyer, Barbara; Dhimal, Meghnath; Gautam, Ishan; Shreshta, Pramod; Baral, Sunita; Phuyal, Parbati; Hartke, Juliane; Magdeburg, Axel; Groneberg, David A.; Ahrens, Bodo; et al.
Abstract: Driven by globalization, urbanization and climate change, the distribution range of invasive vector species has expanded to previously colder ecoregions. To reduce health‐threatening impacts on humans, insect vectors are extensively studied. Population genomics can reveal the genomic basis of adaptation and help to identify emerging trends of vector expansion. By applying whole genome analyses and genotype‐environment associations to populations of the main dengue vector Aedes aegypti, sampled along an altitudinal gradient in Nepal (200–1300 m), we identify putatively adaptive traits and describe the species' genomic footprint of climate adaptation to colder ecoregions. We found two differentiated clusters with significantly different allele frequencies in genes associated to climate adaptation between the highland population (1300 m) and all other lowland populations (≤800 m). We revealed nonsynonymous mutations in 13 of the candidate genes associated to either altitude, precipitation or cold tolerance and identified an isolation‐by‐environment differentiation pattern. Other than the expected gradual differentiation along the altitudinal gradient, our results reveal a distinct genomic differentiation of the highland population. Local high‐altitude adaptation could be one explanation of the population's phenotypic cold tolerance. Carrying alleles relevant for survival under colder climate increases the likelihood of this highland population to a worldwide expansion into other colder ecoregions.